PLANNING FOR MULTIPLE USES OF WATER: LIVELIHOOD ACTIVITIES AND HOUSEHOLD WATER CONSUMPTION IN PERIURBAN COCHABAMBA, BOLIVIA - Duran, Alfredo; Herbas, Daniel; Reynaga, Magaly; Butterworth, John (Águas Subterrâneas, 2004)
This paper presents two methodologies to assess livelihood activities and water use as part of the planning of water supply projects. A case study from peri-urban Tiquipaya, close to the city of Cochabamba in Bolivia, illustrates results from both the rapid and more detailed methodologies presented. The main findings of the case study are that the productive uses of domestic water supplies, particularly irrigating small gardens (huertas) and watering livestock appear to have been underestimated to date, both in their importance for the livelihoods of households in Tiquipaya and in patterns of water use. Currently, water supplies are mainly provided by small locally-managed groundwater-based systems, although there is a contested plan to move towards more centrally-planned systems. It is concluded that the future development of water supply systems in the area is more likely to be sustainable and to meet local needs if productive uses of water at the household level are considered at the planning stage: these activities being particularly dependent upon the availability and cost of domestic water supplies.